2015
DOI: 10.1093/hmg/ddv295
|View full text |Cite
|
Sign up to set email alerts
|

Activating the translational repressor 4E-BP or reducing S6K-GSK3β activity prevents accelerated axon growth induced by hyperactive mTORin vivo

Abstract: Abnormal axonal connectivity and hyperactive mTOR complex 1 (mTORC1) are shared features of several neurological disorders. Hyperactive mTORC1 alters axon length and polarity of hippocampal neurons in vitro, but the impact of hyperactive mTORC1 on axon growth in vivo and the mechanisms underlying those effects remain unclear. Using in utero electroporation during corticogenesis, we show that increasing mTORC1 activity accelerates axon growth without multiple axon formation. This was prevented by counteracting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 64 publications
(83 reference statements)
3
36
0
Order By: Relevance
“…Given that elevated cortical p-S6 and CRMP2, and rescue by S6K1 inhibitor treatment, all occur during the early postnatal life, we predict that the initial growth of subcortical-projecting neurons is over-exuberant in Pten +/− mice. This would be consistent with reports of Pten and mTOR-S6K signalling acting as regulators of axonal growth711. Another factor that could be at play is reduced axonal pruning of subcortical-projecting neurons in Pten +/− mice.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Given that elevated cortical p-S6 and CRMP2, and rescue by S6K1 inhibitor treatment, all occur during the early postnatal life, we predict that the initial growth of subcortical-projecting neurons is over-exuberant in Pten +/− mice. This would be consistent with reports of Pten and mTOR-S6K signalling acting as regulators of axonal growth711. Another factor that could be at play is reduced axonal pruning of subcortical-projecting neurons in Pten +/− mice.…”
Section: Discussionsupporting
confidence: 92%
“…Phosphorylated rpS6 (p-S6) is a readout for mTORC1 signalling, and has been shown to regulate cell size4. Moreover, studies in the mammalian nervous system have shown that mTOR-S6K signalling regulates neuronal soma size, dendritic arborization, axonal growth and connectivity567.…”
mentioning
confidence: 99%
“…Patch‐clamp recordings in the animals reveal increased cell capacitance and decreased membrane resistance in the Rheb CA model. Astrogliosis and microglial activation, and increased axonal length, are observed in the Rheb CA ‐model and in the Depdc5 flox/flox ‐Syn1 Cre mouse . Of interest, as in Tsc2 cKO mice, the degree of mTOR hyperactivity correlates with the severity of epilepsy and associated neuropathology including soma size and misplacement Rheb CA plasmid model .…”
Section: Epileptogenesis and Mtor‐gator Signalingmentioning
confidence: 99%
“…A construct expressing an shRNA against both S6K1 and S6K2 (shS6K1/2, previously used by our laboratory to normalize Rheb CA effects on axon length [35]) was coelectroporated with Rheb CA ; an empty vector was coelectroporated as a control (Fig. S7A).…”
Section: Significancementioning
confidence: 99%